Executive Compensation from Deontological and Utilitarian Ethics: A Literature Review - Christine Gianina Sulistio; Andhita Rosy Febrina; Khusnul Prasetyo (Ilomata International Journal of Social Science, 2026)
This study examines executive compensation within ethical frameworks, particularly deontological and utilitarian ethics, through a focused literature review of ten peer-reviewed journal articles published between 2020 and 2025. The research aims to explore how ethical principles shape executive compensation policies in promoting fairness, transparency, accountability, and social responsibility within corporate governance systems. The selected articles were qualitatively analyzed to identify dominant ethical perspectives and recurring themes related to executive remuneration, without claiming a fully systematic review procedure due to the limited number of studies and the absence of a detailed search and screening protocol. The findings indicate that a majority of the reviewed studies explicitly address the ethical dimensions of executive compensation, reflecting increasing scholarly attention to the alignment between financial incentives and moral responsibilities. From a deontological perspective, executive compensation should be grounded in principles of duty, justice, and respect for stakeholder rights, independent of performance outcomes. In contrast, utilitarian ethics assess compensation practices based on their capacity to maximize collective benefits, including organizational performance, employee welfare, and broader social value. The analysis further demonstrates that these two ethical frameworks can be integratively applied to develop a balanced compensation system that simultaneously emphasizes performance-based rewards and ethical accountability. Moreover, the literature highlights that unethical compensation practices may lead to stakeholder dissatisfaction, reputational risks, and internal organizational conflict. Therefore, embedding ethical considerations into executive compensation structures is essential for fostering responsible leadership, strengthening corporate integrity, reducing inequality, and ensuring the long-term sustainability of corporate governance practices.